The relevance of meritocratic beliefs for redistributive preferences increases with income - Irene Pa\~neda-Fernández; Jonne Kamphorst; Arnout van de Rijt; Balaraju Battu (Social Science Research, 2026)
A leading explanation for why in democratic societies the rich are not taxed more is that meritocratic beliefs breed tolerance for inequality. We problematize this account by claiming that, unlike the rich, the poor support greater redistribution regardless of how meritocratic they perceive society to be. The claim is tested using a cross-national survey and a preregistered experimental game that exogenized both income and perceptions of meritocratic fairness. Analysis of both survey and experimental data supports the proposed interaction effect between income and perceived meritocratic fairness on demand for redistribution. We conclude that while meritocratic beliefs can explain why the rich do not support more redistribution, it fails to explain the poor's inequality acceptance.
Keywords: 330; Inequality; Redistribution; Meritocracy; Income; Fairness